Pengaruh Motivasi Terhadap Permintaan Industri Pariwisata - I.G.N. Wedagama; J Aditya Sari (Sekolah Tinggi Pariwisata Sahid Surakarta, 2009)
The decision making for traveling is generally more complicated than it is for purchasing other luxurious necessities. There are factors to be taken into attention to maximize the value of the money we have spent on traveling for the family. The traveler’s motives are influenced by the type, destination, and social networking, either before or during the trip. Some examples are people travel for having new experience with environment, meeting the locales, understanding the culture, revitalizing the family relationship, resting and relaxing, rejuvenating, self protecting and security, respecting social status, and rewarding oneself of certain accomplishments. In the relation with travelers’ behavior, either individual or group, it is important to look further into such motives.